Kenali Potensimu: Mengenal Bakat dan Minat Sejak Usia Dini untuk Meningkatkan Percaya Diri dan Perencanaan Masa Depan - Purba, Novia; Haryadi, Fellicya Audreynadhine (Universitas Dinamika, 2025)
Talent and interest are important components that are interconnected in helping children develop, especially in achieving educational goals. Talent is an innate potential that needs to be trained and developed in a structured manner, while interest is an individual's tendency to focus on things they like. Lack of attention to children's talents and interests can hinder the development of their potential. In addition, lack of facilities and pressure from schoolwork are often the main obstacles. Psychoeducation is one of the effective interventions to help children and teachers recognize and develop children's talents and interests optimally. This community service activity was carried out at SDS Punna Karya, Curug, Tangerang, involving students in grades 1–6 and teachers as participants. This activity is intended to provide students with a new understanding of the importance of identifying their interests and talents to discover their potential, set goals, and stay motivated to learn. For one month (October 11 to November 2, 2023), this program was implemented with a qualitative approach through the psychoeducational method. The results of the community service showed that providing psychoeducation helped students understand their interests and talents, increased their motivation to learn, and encouraged them to be more confident in exploring their potential. In addition, support from the school, teachers, and the surrounding environment plays an important role in the success of developing children's talents and interests. By maximizing their potential, children are expected to be able to achieve optimal results in their education and life.